Knowledge-Based Competencies Necessary for the Frontline Construction Supervisor : Improving Safety through Knowledge - Hardison, Dylan (East Carolina University, 2012)
Evaluating supervisor competency levels has been a management challenge since the beginning of supervisory roles in the construction process. Supervisors perform a critical role in the workplace with respect to workplace safety and health. Supervisors are the driving component of the operational aspects of management systems and often convey messages from upper level management directly to line level work force. As a supervisor serves as a liaison for the line level work force, it is vitally important supervisors have a clear understanding of his roles and responsibilities within his organization. As upper level management strives to improve the safety record of an organization, the supervisor must be valued as a key component of an organizations struggle to help establish a proactive safety culture. The issue presents itself when the true level of supervisor competency cannot be determined by management. The purpose of this paper is to identify the key knowledge-based competencies that are suggested to be the most important to the construction supervisor with respect to improving construction site safety performance.
Keywords: Management; Competency; Occupational; Safety; Supervisors; Building--Superintendence--United States; Construction industry--United States--Management; Construction industry--Employees--Training of--United States